DETECTION OF BRAF MUTATION IN MELANOMA FOUND IN TISSUE AND CFDNA BY USING A HIGHLY SENSITIVE PNA-CLAMP PCR. - MIKAEEL, REGER R.; EVANGELOU, ISAVELLA; BILBIE, JOSHUA; PRINGLE, JAMES HOWARD; SALDANHA, GERALD (Journal of Duhok University, 2018)
Malignant melanoma results from ongoing activation of the mitogen activated protein kinases(MAPK ) pathway, commonly driven by mutations in BRAF. Several selective inhibitors of this pathway are used clinically, most notably the Vemurafenib and Dabrafenib. Different methods for BRAF mutation detection exist in the United Kingdom, including pyrosequencing, COBAS test and Sanger sequencing. However, there is significant variability in the analytical sensitivity of these tests. A highly sensitive PCR assay was developed to detect low tumor cell percentage of 0.1% in formalin fixed paraffin embedded (FFPE) tissue and plasma. The assay was developed on stable cell lines containing BRAF (codon 600) mutations. Peptide nucleic acid (PNA) Clamp PCR was used for the selective amplification of DNA target sequences. Total DNA was extracted from 48 FFPE tissues and 20 blood plasma (14 matched) stage II-IV melanoma patients and screened for BRAF mutations. Results were correlated with COBAS test data and clinical parameters. PNA Clamp PCR on FFPE tissue showed 46% (n=22) BRAF mutants. Four more BRAF mutant cases were identified using PNA clamp methodology when compared to COBAS. Sample cases were independently tested. Matched samples showed 85% (n=12) correlation for BRAF mutation status (6 + ve, 4 – ve, 2 with no residual tumor burden). There were two cases which were positive for COBAS test and PNA Clamp PCR but negative for cfDNA. This demonstrates an innovative and highly sensitive technique for the detection of the common driver mutations in melanoma using exceptionally low tumor burden samples, representing a useful tool for future research and clinical application.